Oligo Hyaluronan‐Coated Silica/Hydroxyapatite Degradable Nanoparticles for Targeted Cancer Treatment. Issue 13 (30th April 2019) - Kang, Yao; Sun, Wen; Li, Shuyi; Li, Mingle; Fan, Jiangli; Du, Jianjun; Liang, Xing‐Jie; Peng, Xiaojun
Abstract: Targeted drug delivery systems (TDDSs) provide a promising approach to overcome the side effect of traditional chemotherapy by specific tumor targeting and drug release. Hyaluronan (HA), as a selective CD44 targeting group, has been widely used in TDDSs for chemotherapy. However, different molecular weight HAs would demonstrate different binding ability to CD44, which may result in different therapeutic effects. Herein, a silica/hydroxyapatite (MSNs/HAP) hybrid carrier loaded with anticancer drug doxorubicin (DOX) (DOX@MSNs/HAP) is fabricated. HA and oligo HA (oHA) are coated onto the nanoparticles (HA‐DOX@MSNs/HAP, oHA‐DOX@MSNs/HAP), respectively, to investigate their performance in tumor targeting ability. oHA‐DOX@MSNs/HAP shows much higher efficiency cellular uptake and drug release in tumor regions due to more effective CD44 targeting of oHA. Thus, the anticancer effect of oHA‐DOX@MSNs/HAP is significantly enhanced compared to HA‐DOX@MSNs/HAP, as demonstrated in a tumor‐bearing mouse model. This study may enable the rational design of nanodrug systems for future tumor‐targeted chemotherapy. Abstract : Oligo hyaluronan (oHA) coated silica/hydroxyapatite degradable nanoparticles (oHA‐DOX@MSNs/HAP) demonstrate much higher efficiency cellular uptake and drug release in tumor regions than general hyaluronan coated nanoparticles (HA‐DOX@MSNs/HAP), due to the more effective CD44 targeting of oHA. The anticancer effect of oHA‐DOX@MSNs/HAP is significantly enhanced, as demonstrated in a tumor‐bearing mouse model.